Colaboradores - Torres, Laura Christiane (Faculdade de Filosofia e Ciências, 2016)
Carla Cristina VrecheCésar Francisco Cárdenas Dávila Florencia Rubiolo Fred MacielGabriel Campos Fernandino José G. Vargas-HernándezLaurindo Paulo Ribeiro TchinhamaLeonardo Luiz Silveira da Silva Marcos Valle Machado da SilvaMatheus de Carvalho HernandezPaulo Duarte